A new recombinant factor VIII: from genetics to clinical use - Santagostino E (Dove Medical Press, 2014)
Elena Santagostino Angelo Bianchi Bonomi Hemophilia and Thrombosis Center, Fondazione IRCCS Ca’ Granda, Ospedale Maggiore Policlinico, Milan, Italy Abstract: Advances in recombinant technology and knowledge about coagulation factor VIII (FVIII) are building a platform for new therapeutic options in patients with hemophilia A. The development of turoctocog alfa, a novel, high-purity, third-generation, B-domain truncated recombinant FVIII, has been produced and formulated without the use of animal-derived or human serum-derived components, in the wake of understanding of the new biochemical characteristics of FVIII, namely its protein structure, and glycosylation and sulfating patterns. Culture conditions and a five-step purification process have been developed to optimize the safety of turoctocog alfa. The results of two pilot clinical trials using turoctocog alfa confirmed high safety levels, with no patient developing inhibitors during the period of observation. The purpose of this review is to describe briefly the molecular and biological properties of turoctocog alfa, together with details of its clinical development, with emphasis on the needs of patients with hemophilia A. Keywords: hemophilia A, recombinant factor VIII, turoctocog alfa, purification, inhibitor, safety